(untitled) (Nóema, 2013)
The present essay aims to investigate the role and the relevance of the Agent and its subjective dimension in the scope of Natural Sciences. Science pursues an ideal of absolute objectivity, with all individual instances totally banished. However, the analysis of the process of acquiring new scientific concepts, observed in its becoming, shows that individual cognizances and subjective perceptions constantly intervene all along the path of a notion through the human knowledge. The adoption of protocols not grounded on quantitative indicators and unbiased formal procedures represents an epistemological base larger than the ordinary framework, acting in synergy with the weighting of the operating subjects. These components do not undermine the overall reliability, but rather they disclose a greater discernment potential, merging into a criterion of truth inclusive and shared, we may call "over-objectivity".